Vertical density representation and its applications - Troutt, Marvin D. (Marvin Dean) (World Scientific, 2004)
This book presents a new research topic in statistics? verticaldensity representation (VDR). The theory of VDR has been found to beuseful for developing new ideas and methodologies in statistics andmanagement science. The first paper related to VDR appeared in1991. Several others have since been published and work is continuingon the topic. The purpose of this book is to survey the resultspresented in those papers and provide some new, unpublished results. VDR may be regarded as a special kind of transformation. By assumingthat a variate is uniformly distributed on the contours of a givenfunct.